Aplicación de colores neón en murales como tendencias innovadoras de publicidad - Morales Ortega, Cristian Fernando (2022)
Currently, neon colors are a fundamental part of innovation in advertising, however, it is not widely used by commercial premises, without taking into account that this type of proposal generates expectation and notoriety in the face of other advertising proposals. This research focused on applying neon colors in murals as innovative advertising trends in three commercial premises in the city of Riobamba, used as a new communication strategy in different areas and themes in the commercial field. For the development of the research, the qualitative and quantitative approach was used, based on the analytical-descriptive methodology, in which the interview and survey were used, as data collection techniques, the sample studied corresponded to the population of the Riobamba canton and the interviews were directed to owners and clients of each store. With the results obtained, it was found that the advertising murals with neon paint responded to the function of attracting and causing admiration on the part of the client, thanks to the intensity caused by the neon color it turned out to be attractive, both for children, young people and adolescents.